A simple strategy based on a highly fluorinated polymer blended with a fluorinated polymer containing phosphonic acid to improve the properties of PEMFCs. (27th June 2019) - Labalme, Etienne; David, Ghislain; Buvat, Pierrick; Bigarre, Janick
Abstract : Phosphonic acid containing fluorinated blend membranes led to new PEMFCs with a proton conductivity of 40 mS cm −1 at 80 °C. Abstract : In order to enhance the thermo-chemical and mechanical proton exchange membrane (PEM) properties, a series of five blend membranes made from poly(vinylidene fluoride- co -chlorotrifluoroethylene) (poly(VDF- co -CTFE)) with a fluorinated copolymer containing phosphonic acid was synthesised. The mechanical properties of these blend membranes were assessed by dynamic mechanical analysis (DMA). In order to determine the influence of the fluorinated copolymer on the blend membrane morphology, a SAXS study was performed. The presence of the fluorine atoms in poly(VDF- co -CTFE) allows us to obtain membranes with a better structuration, but also to enhance the oxidative stability in the presence of radicals. The best result obtained shows a proton conductivity of 40 mS cm −1 at 80 °C under fully hydrated conditions.